Peran Perceived Value Memoderasi Pengaruh Price Elasticity Terhadap Purchase Decision pada Generasi Z - Novita Putri Diantati; Naadiya Aisyah Alfadlilah (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Modern life is inseparable from the growth of marketplaces and e-commerce, as Shopee has the largest traffic share in Indonesia. Promotional strategies provide opportunities for consumers to obtain attractive offers, while price elasticity remains a key factor influencing both attraction and retention. In addition, perceived value captures consumer’s evaluations of product benefits and quality, which ultimately shapes their purchase decisions. This study aims to analyze the moderating role of perceived value in the relationship between price elasticity and purchase decision. A quantitative approach was employed, involving 122 students of Universitas Islam Balitar as respondents, selected through accidental sampling technique. The findings reveal that price elasticity significantly affects purchase decisions, confirming its role in determining consumer choice. In addition, perceived value variable is proven to moderate and weaken the relationship. Consumers with high perceived value tend to be less sensitive in price changes, whereas consumers with low perceived value are easily influenced even by relatively small price fluctuations.